Evaluation of different techniques for the diagnosis of bovine babesiosis - Renjitha T S (Department of Veterinary Parasitology, College of Veterinary and Animal Sciences, 2003)
Different techniques to diagnose bovine babesiosis were evaluated by screening 71 cattle presented at the various Veterinary Hospitals of Thrissur and Ernakulam districts and those maintained at the University Livestock Farm, Mannuthy and the Cattle Breeding Farm, Thumburmuzhi with symptoms suggestive of the disease. The techniques employed were examination ofGiemsa stained blood smears, examination of ticks collected from suspected animals and serological tests like the Indirect Fluorescent Antibody Test (IF AT) and Slide- Enzyme Linked Immunosorbent Assay (Slide-ELISA). Among the 71 cattle, 11 were suffering from an acute illness whereas 60 showed only subclinical symptoms. Examination of Giemsa stained blood smear could detect Babesia bigemina organisms in 9 (12.68 per cent) of the total samples, which were mainly from the acutely infected cattle, except for one, that was obtained from a subclinically infected calf. The principal vector of babesiosis was identified as Boophilus annulatus in the present study. Parasitic masses indicative of the organisms were identified from the various tick tissues dissected and stained with methyl green pyronine. Considering the ticks as positive on detection of developmental stages of the parasite in any of the tissues, ticks from 27 (54 per cent) out of total 50 animals were interpreted as positive. The IFAT detected B. bigemina antibodies in 37 (52.11 per cent) and Slide-ELISA in 39 (54.93 per cent) sera out of 71 samples that were screened. These two serological techniques were found to be equally efficient, with Slide- ELISA proving more suitable for use as a field diagnostic test.